Design of a high efficiency rectifier with wide bandwidth and input power range based on the time reversal duality of power amplifier - Defu Wang; Xuan Anh Nghiem; Muh-Dey Wei; Renato Negra (2015 European Microwave Conference (EuMC), 2015)
This paper presents the concept and measurements of a new microwave rectifier based on the time reversal duality of power amplifiers. It is shown that the proposed rectifier can simultaneously provide high efficiency at large input power range over much more improved bandwidth compared to the conventional rectifier from time reversal duality. It is also reported that the proposed rectifier allows reconfiguration of the efficiency at input power range without placing the tunable elements. A 10 W wideband power amplifier with 79%drain efficiency at 1.85 GHz is used to validate the concept. By making the gate bias network short-terminated and replacing the drain termination with the DC load resistor for power amplifier, the circuit can operate as microwave rectifier with taking part of bandwidth from power amplifier. Measurements show the efficiency bandwidth with larger than 70 % rectifying efficiency at 15 dB input power range over a 1.7–1.95 GHz frequency range. The measurements thereby validate the presented concept and demonstrate the potential of the proposed rectifier for use in future wireless energy harvesting applications.